2021
DOI: 10.3390/ijerph181910447
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Medication: From a Simple Concept to Complex Practical Aspects

Abstract: Off-label use of drugs is widely known as unapproved use of approved drugs, and it can be perceived as a relatively simple concept. Even though it has been in existence for many years, prescribing and dispensing of drugs in an off-label regimen is still a current issue, triggered especially by unmet clinical needs. Several therapeutic areas require off-label approaches; therefore, this practice is challenging for prescribing physicians. Meanwhile, the regulatory agencies are making efforts in order to ensure a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 82 publications
0
20
0
1
Order By: Relevance
“…Bellis et al found an increased risk related to off label drugs used in oncological practice and the result became statistically insignificant when oncology patients were excluded ( Bellis et al, 2014 ). Thus, it is possible that the greater risk of ADRs observed by the other studies resulted from a different pattern of off-label drug use ( Rusz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…Bellis et al found an increased risk related to off label drugs used in oncological practice and the result became statistically insignificant when oncology patients were excluded ( Bellis et al, 2014 ). Thus, it is possible that the greater risk of ADRs observed by the other studies resulted from a different pattern of off-label drug use ( Rusz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 97%
“…(3) Thus, approaching patient concerns in a multifactorial approach can help target underlying mechanisms for illness and behavior, such as the anxiety component of vomiting seen in the two cases. Second, when research is unavailable for rare, complicated cases, evidence-based decision making is needed 7 . Due to the complex medical history of some cases, off-label prescriptions of psychiatric medications may be warranted.…”
Section: Discussion Conclusionmentioning
confidence: 99%
“…В литературе упоминается синоним термина «off -label use» -«an unlabeled use» [8]. Дефиниция «off -label use» отличается от значения термина «незарегистрированный препарат» [11]. Под незарегистрированным ЛП подразумевается продукт, не имеющий государственной регистрации на территории РФ и отсутствующий в Государственном реестре лекарственных средств.…”
Section: понятие определения Off -Labelunclassified